Epigenetic alterations in hippocampus of SAMP8 senescent mice and modulation by voluntary physical exercise - Cosín-Tomás, Marta; Alvarez-López, María J.; Sanchez-Roige, Sandra; Lalanza, Jaume F.; Bayod, Sergi; Sanfeliu, Coral; Pallas, Merce; Escorihuela, Rosa M.; Kaliman, Perla (Frontiers in Aging Neuroscience, 2014)
The senescence-accelerated SAMP8 mouse model displays features of cognitive decline and Alzheimer's disease. With the purpose of identifying potential epigenetic markers involved in aging and neurodegeneration, here we analyzed the expression of 84 mature miRNAs, the expression of histone-acetylation regulatory genes and the global histone acetylation in the hippocampus of 8-month-old SAMP8 mice, using SAMR1 mice as control. We also examined the modulation of these parameters by eight weeks of voluntary exercise. Twenty-one miRNAs were differentially expressed between sedentary SAMP8 and SAMR1 mice and seven miRNAs were responsive to exercise in both strains. SAMP8 mice showed alterations in genes involved in protein acetylation homeostasis such as Sirt1 and Hdac6 and modulation of Hdac3 and Hdac5 gene expression by exercise. Global histone H3 acetylation levels were reduced in SAMP8 compared with SAMR1 mice and reached control levels in response to exercise. In sum, data presented here provide new candidate epigenetic markers for aging and neurodegeneration and suggest that exercise training may prevent or delay some epigenetic alterations associated with accelerated aging.